2015
DOI: 10.1007/s00394-015-1080-1
|View full text |Cite
|
Sign up to set email alerts
|

No association between blood telomere length and longitudinally assessed diet or adiposity in a young adult Filipino population

Abstract: Purpose Telomeres, DNA-protein structures that cap and protect chromosomes, are thought to shorten more rapidly when exposed to chronic inflammation and oxidative stress. Diet and nutritional status may be a source of inflammation and oxidative stress. However, relationships between telomere length (TL) and diet or adiposity have primarily been studied cross-sectionally among older, overweight/obese populations and yielded inconsistent results. Little is known about the relationship between diet or body compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 105 publications
(168 reference statements)
0
15
0
Order By: Relevance
“…Another study on 840 adults indicated that the consumption of processed meat was inversely associated with TL ( Nettleton et al, 2008 ). In the study of Betancourt et al, processed meat, grilled meat, oil, and beverages were associated with shorter TL ( Bethancourt, 2014 ). Per other studies, high intake of processed meat leads to the formation of inflammatory mediator compounds and increases the risk of numerous cancers such as breast cancer ( Cho et al, 2006 ), diabetes ( Pan et al, 2011 ) and cardiovascular diseases (CVD) ( Micha, Wallace, & Mozaffarian, 2010 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Another study on 840 adults indicated that the consumption of processed meat was inversely associated with TL ( Nettleton et al, 2008 ). In the study of Betancourt et al, processed meat, grilled meat, oil, and beverages were associated with shorter TL ( Bethancourt, 2014 ). Per other studies, high intake of processed meat leads to the formation of inflammatory mediator compounds and increases the risk of numerous cancers such as breast cancer ( Cho et al, 2006 ), diabetes ( Pan et al, 2011 ) and cardiovascular diseases (CVD) ( Micha, Wallace, & Mozaffarian, 2010 ).…”
Section: Discussionmentioning
confidence: 93%
“…In another study, a direct relationship was reported between the consumption of fruits and TL in men, but this relationship was not identified in women ( Tiainen et al, 2012 ). Another study reported that the consumption of fish, fruits and vegetables are positively associated with TL ( Bethancourt, 2014 ). But some studies such as Gu et al ( Gu et al, 2015 ) and several other studies reported no significant relationship between vegetables and/or fruits and TL ( Gu et al, 2015 ; Tiainen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The derivation of these PCs have been described previously (Croteau‐Chonka et al, ; Croteau‐chonka et al, ; Wu et al, ). As in previous analyses (Bethancourt et al, ; D. Eisenberg et al, ; Ryan et al, ), the bivariate association between the first 10 PCs and TL were tested. The top PCs up to and including the last one showing a significant bivariate association with TL (10 total) were retained as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…The derivation of these principal components have been described previously (Wu et al, 2011; Croteau-Chonka et al, 2012; Croteau-Chonka et al, 2011). As in previous analyses (Bethancourt et al, 2015), the bivariate association between the first ten principal components and TL were tested. The top principal components up to and including the last one showing a significant bivariate association with TL were retained as control variables.…”
Section: Methodsmentioning
confidence: 99%